Bystander signals from low- and high-dose irradiated human primary fibroblasts and keratinocytes modulate the inflammatory response of peripheral blood mononuclear cells. (19th January 2023) - Testard, Isabelle; Garcia-Chartier, Elizabeth; Issa, Amani; Collin-Faure, Véronique; Aude-Garcia, Catherine; Candéias, Serge M
Abstract: Irradiated cells can propagate signals to neighboring cells. Manifestations of these so-called bystander effects (BEs) are thought to be relatively more important after exposure to low- vs high-dose radiation and can be mediated via the release of secreted molecules, including inflammatory cytokines, from irradiated cells. Thus, BEs can potentially modify the inflammatory environment of irradiated cells. To determine whether these modifications could affect the functionality of bystander immune cells and their inflammatory response, we analyzed and compared the in vitro response of primary human fibroblasts and keratinocytes to low and high doses of radiation and assessed their ability to modulate the inflammatory activation of peripheral blood mononuclear cells (PBMCs). Only high-dose exposure resulted in either up- or down-regulation of selected inflammatory genes. In conditioned culture media transfer experiments, radiation-induced bystander signals elicited from irradiated fibroblasts and keratinocytes were found to modulate the transcription of inflammatory mediator genes in resting PBMCs, and after activation of PBMCs stimulated with lipopolysaccharide (LPS), a strong inflammatory agent. Radiation-induced BEs induced from skin cells can therefore act as a modifier of the inflammatory response of bystander immune cells and affect their functionality.